In the pursuit of new social neurons. Neurogenesis and social behavior in mice: A systematic review - García-Gómez, Lydia; Castillo-Fernández, Iker; Perez-Villalba, Ana (Frontiers in Cell and Developmental Biology, 2022)
Social behaviors are becoming more relevant to understanding our nervous system because relationships with our peers may require and modulate adult neurogenesis. Here we review the pieces of evidence we have to date to understand if social behaviors in mice can diverge by modulating adult neurogenesis or if social behaviors and the social environment can drive a change in neurogenic processes. Social recognition and memory get deeply affected after antimitotic drugs and irradiation, while GFAP transgenic mice may run with lower levels of social discrimination. Interestingly, social living conditions can reach a big impact on neurogenesis. Social isolation and social defeat reduce the number of new neurons while social dominance and enrichment of social environment increase their number. These new “social neurons” trigger functional modifications with amazing transgenerational effects. All of this suggests that we are facing two bidirectional intertwined variables and the great challenge now is to understand the cellular and genetic mechanisms that will allow us to use this relationship therapeutically.